Items Wrongfully Seized in Corruption Cases - Tirtakusuma, Andreas Eno (Penerbit Mandalika Indonesia, 2025)
This paper examines the legal mechanism for third parties to file objections to the wrongful seizure of items, focusing on the applicability of Supreme Court Regulation (PERMA) No. 2 of 2022. The approaches used include legislative, case-based, and conceptual approaches. The Djoko Susilo case serves as a concrete example, where the defendant's family filed an objection to the seizure of assets that were not proceeds of a crime. PERMA No. 2 of 2022 provides a procedure for filing objections in an orderly, swift, and cost-free manner, while avoiding overlap between civil and administrative jurisdictions. However, the success of the objection is heavily dependent on proving the